Reliability and validity of three clinical methods to measure lower extremity muscle power - Pontiff, M. E.; Li, L.; Moreau, N. G. (International Journal of Kinesiology & Sports Science, 2021)
Background: Lower extremity muscle power is critical for daily activities and athletic performance in clinical populations. Objective: The purpose of this study was to determine the reliability and validity of 3 clinically feasible methods to measure lower extremity muscle power during a leg press. Methods: Ten of 26 subjects performed 2 sessions of 5 submaximal leg presses separated by 3-7 days in this repeated-measures cross-sectional design; the remaining performed 1 test session. Power was calculated independently for each method [simple video, linear position transducer, and accelerometer] and compared to the reference force plate. Test-retest reliability was evaluated using intraclass correlation coefficients (ICC). Pearson`s correlation coefficient (r), Bland-Altman plots with 95% limits of agreement (LOA), and mean bias percentages (%) were used to determine relative and absolute validity. Results: Power measures were reliable for all methods (ICC=.97-.99). All were highly correlated with the force plate (r=.96-.98). Mean bias was -0.8% (LOA: -16.57% to 14.98%) (video), -13.21% (LOA: -23.81% to -2.61%) (position transducer) compared to the force plate. Proportional bias was observed for accelerometry. Conclusion: All methods were reliable and highly correlated with the force plate. Only the video and position transducer demonstrated absolute validity. The position transducer was the most feasible method because of its simplicity and accuracy in measuring power.